Letter - Lizaso, Jose I. de
012a-0131-001 Autonomous Government of Euzkadi London Delegation. Spanish Embassy, 24, Belgrave Square S W.1 P.1. 28th February, 1938. The Editor, Sir, I have pleasure in enclosing herewith for your interest a translation of an official report by the Basque Minister of Justice, Senor Don J. M. de Leizaola, on the administration of justice in the Basque country before and after the occupation by the Franco authorities. The fully documented lists will, I hope, provide a background of fact to a matter which has been the subject of considerable, and often uninformed, controversy during the past few months. Yours faithfully Jose I. de Lizaso Enc: 292/946/12a/131